Technical note: Towards atmospheric compound identification in chemical ionization mass spectrometry with pesticide standards and machine learning - F. Bortolussi; H. Sandström; F. Partovi; F. Partovi; J. Mikkilä; P. Rinke; P. Rinke; P. Rinke; P. Rinke; M. Rissanen; M. Rissanen (Atmospheric Chemistry and Physics)
Chemical ionization mass spectrometry (CIMS) is widely used in atmospheric chemistry studies. However, due to the complex interactions between reagent ions and target compounds, chemical understanding remains limited and compound identification difficult. In this study, we apply machine learning to a reference dataset of pesticides in two standard solutions to build a model that can provide insights from CIMS analyses in atmospheric science. The CIMS measurements were performed with an Orbitrap mass spectrometer coupled to a thermal desorption multi-scheme chemical ionization inlet unit (TD-MION-MS) with both negative and positive ionization modes utilizing Br−, <msubsup>O2-</msubsup><svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="17pt" height="16pt" class="svg-formula" dspmath="mathimg" md5hash="0874c22b59d147314cd2f8e88d131371"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-25-685-2025-ie00001.svg" width="17pt" height="16pt" src="acp-25-685-2025-ie00001.png"/></svg:svg>, H3O+ and (CH3)2COH+ (AceH+) as reagent ions. We then trained two machine learning methods on these data: (1) random forest (RF) for classifying if a pesticide can be detected with CIMS and (2) kernel ridge regression (KRR) for predicting the expected CIMS signals. We compared their performance on five different representations of the molecular structure: the topological fingerprint (TopFP), the molecular access system keys (MACCS), a custom descriptor based on standard molecular properties (RDKitPROP), the Coulomb matrix (CM) and the many-body tensor representation (MBTR). The results indicate that MACCS outperforms the other descriptors. Our best classification model reaches a prediction accuracy of 0.85 ± 0.02 and a receiver operating characteristic curve area of 0.91 ± 0.01. Our best regression model reaches an accuracy of 0.44 ± 0.03 logarithmic units of the signal intensity. Subsequent feature importance analysis of the classifiers reveals that the most important sub-structures are NH and OH for the negative ionization schemes and nitrogen-containing groups for the positive ionization schemes.